E‐beam pumped mid‐UV sources based on MBE‐grown AlGaN MQW. Issue 5 (19th February 2015) - Ivanov, S. V.; Jmerik, V. N.; Nechaev, D. V.; Kozlovsky, V. I.; Tiberi, M. D.
<x xml:space="preserve">Abstract</x> A 60 mW output power has been achieved in mid‐UV (λ = 270 nm) spontaneous sources with electron‐beam pulse‐scanning pumping, fabricated from AlGaN MQW heterostructures grown by PA MBE on c‐Al2O3 substrates. Under the CW pumping at much lower excitation power density the mid‐UV sources demonstrate a 4.7 mW output power. In that regime the power efficiency of the structures is about 0.24%, while their internal quantum efficiency is estimated to be as high as 50%.